FRI0168 Safety, Tolerability, Pharmacokinetics (PK) and Pharmacodynamics (PD) of BI 655064, An Antagonistic Anti-CD40 Antibody in Healthy Volunteers. (9th June 2015) - Schwabe, C.; Wagner, F.; Filler, I.; Albulescu, M.; Rose, P.; Emerson, B.; Doan, T.; Rosenstock, B.; Joseph, D.; Hilbert, J.; Schölch, C.; Habeck, J.; et al.
Abstract : Background: The CD40-CD40L pathway may play a major role in autoimmune disorders like rheumatoid arthritis (RA). Blocking this pathway may be a promising new treatment for RA-patients. BI 655064 is a novel humanized antagonistic anti-CD40 monoclonal antibody, free of agonistic activity and without antibody-dependent cellular- or complement-dependent cytotoxicity. BI 655064 binds human CD40 on B cells in whole blood with an EC90 of 6.85±0.74 nM. Objectives: BI 655064 was investigated in healthy volunteers to assess safety, tolerability, PK and PD after single and multiple dosing. Methods: In a single-blinded randomized, placebo-controlled trial in healthy subjects, BI 655064 was administered to 72 male subjects in increasing single doses of 0.2-120 mg i.v. and 40-120 mg s.c. A double-blinded multiple rising dose study was conducted in 40 male and female subjects at doses of 80-240 mg q1w s.c. for 4 weeks. Blood samples were analyzed for PK, CD40-receptor occupancy (RO) and inhibition of CD40L-induced CD54-upregulation throughout the entire trial duration. Results: All doses of BI 655064 were well tolerated in both studies. There was no-drug related serious adverse event (AE) or significant AE reported. Reported AEs were mainly of mild intensity and did not show a dose-relationship. There was no significant difference in the total number of subjects with AE [BI 655064: 47/86 (54%) vs. placebo: 16/26 (61%)] or category of reported AEs between subjects treated with BI 655064 or placebo (combined data from both studies). The most frequently reported AEs were headache (BI 655064 23% vs. placebo 19%) and upper respiratory tract infection (BI 655064 13% vs placebo 12%) in both studies (combined data). There was no evidence of thromboembolism or bleeding, no hypersensitivity reaction, no cytokine release and no relevant change in safety laboratory tests including coagulation parameters. BI 655064 plasma exposure increased in a supra-proportional manner indicating target mediated drug clearance with a terminal half-life ranging between 6 and 13 days. At single i.v. doses of 20 mg and higher, there was >90% RO and >90% inhibition of CD40L-induced CD54 upregulation for 24 hours after dosing. Single doses of 120 mg i.v. or s.c resulted in >90% RO and >90% inhibition of CD54 upregulation for at least one week. After multiple dosing, persistent >90% RO and >90% inhibition of CD40L-induced CD54 upregulation was maintained for the entire treatment period and for 3 weeks after the last dose for all doses of 120 mg q1w and above. Conclusions: Early trials with BI 655064 show a favorable clinical safety profile and high potential to block the CD40-CD40L pathway supporting clinical trials with BI 655064 in RA-patients. Disclosure of Interest: C. Schwabe Employee of: Auckland Clinical Studies, F. Wagner Employee of: Charité Research Institute, I. Filler Employee of: Charité Research Institute, M. Albulescu Employee of: Boehringer-Ingelheim, P. Rose Employee of: Boehringer-Ingelheim, B. Emerson Employee of: Boehringer-Ingelheim, T. Doan Employee of: Boehringer-Ingelheim, B. Rosenstock Employee of: Boehringer-Ingelheim, D. Joseph Employee of: Boehringer-Ingelheim, J. Hilbert Employee of: Boehringer-Ingelheim, C. Schölch Employee of: Boehringer-Ingelheim, J. Habeck Employee of: Boehringer-Ingelheim, R. Thiedmann Employee of: Boehringer-Ingelheim, S. Padula Employee of: Boehringer-Ingelheim, J. Steffgen Employee of: Boehringer-Ingelheim